CALCULATION OF COMPENSATING SUSCEPTANCE FOR A THREE-WIRE NET - Sirotin, Iu. A. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2014)
A problem of inactive power compensation in a three-wire three-phase network under asymmetrical sinusoidal voltage is considered. An algorithm for calculating susceptance of a Δ-compensator for the total current component active power of which equals zero is introduced. Examples of calculation are given.